Fetal Outcome among Women with Postdate Pregnancy - Afridi, Yasmeen; Jehangir, Rani; Inam Ullah; Kousar Robeen; Muhammad, Anees; Saima Khattak (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: The study aimed to determine the mode of delivery and fetal outcome among women with postdated pregnancies. METHODOLOGY: This cross-sectional study was conducted from July to December 2020 in the Department of Gynecology, Hayatabad Medical Complex, Peshawar. A total of 287 women with postdated pregnancies (beyond 41 weeks) were selected through a convenient sampling technique for the study and followed to detect expected fetal outcomes. All women of age 20-45 with no signs of labor onset and cepahlic presentation of singleton pregnancy were included, while women with retained placenta detected by ultrasound, women with a medical disorder like coagulopathies (Haemophilia, Von Willebrand disease, Thrombocytopenia, DIC, Protein S deficiency, Protein C deficiency) detected by the specific investigation were excluded from the study. Data was analyzed using SPSS version 20. RESULTS: The mean age of the sample was 30.5 years, with a standard deviation of 6.1 years. The mean parity of the sample was 2.1±1.5. The mean BMI of the sample was 26.1±3.8kg/m2. On follow-up, fetal distress in 16%, macrosomia in 18.5%, birth asphyxia in 18.1%, meconium aspiration in 8.4% and NICU admission in 9.1%. None of the neonates died in this study. CONCLUSION: Postdated pregnancy carries a high risk of fetal distress, macrosomia and birth asphyxia. We recommend more large-scale surveys as well as trials to determine the efficacy of induction before pregnancy enters the postdate period and reduce the morbidity and mortality due to postdate pregnancies.